Preparation, Evaluation and Bioavailability Studies of Eudragit Coated PLGA Nanoparticles for Sustained Release of Eluxadoline for the Treatment of Irritable Bowel Syndrome - Anwer, Md. K.; Al-Shdefat, Ramadan; Ezzeldin, Essam; Alshahrani, Saad M.; Alshetaili, Abdullah S.; Iqbal, Muzaffar (Frontiers in Pharmacology, 2017)
Eluxadoline is a newly approved orally administered drug used for the treatment of Irritable Bowel Syndrome with Diarrhea. It is reported as a poorly water-soluble drug due to which its dissolution rate and oral bioavailability are very poor. In this work, initially various plain PLGA nanoparticles (NPs) (F1-F4) were prepared and optimized based on particle size, PDI, zeta potential and percent drug entrapment efficiency (EE). The developed plain NPs (F1-F4) showed average particle size ranging from 260.19-279.76 nm with smooth surface and entrapment efficiency of 17.83-56.29%. The optimized plain NPs (F3) had particle size of 273.76±7.25nm with a low PDI value 0.327, zeta potential ‒ 30.63±2.47mV and % EE of 56.29±2.56%. The optimized F3 NPs was further submitted for enteric coating using Eudragit S100 polymer and evaluated in terms of particles characterization, in vitro release and pharmacokinetic studies in rats. The bioavailability of plain and coated nanaoparticles were enhanced by 6.8 and 18.5 fold, respectively compared to normal suspension. These results revealed that the developed coated NPs could be used for its oral delivery for an effective treatment of Irritable Bowel Syndrome with Diarrhea.